Adult vaccination coverage levels among users of complementary/alternative medicine - results from the 2002 National Health Interview Survey (NHIS) - Bardenheier Barbara H; Kennedy Allison; Cullen Karen A; Stokley Shannon (BMC, 2008)
Abstract Background While many Complementary/Alternative Medicine (CAM) practitioners do not object to immunization, some discourage or even actively oppose vaccination among their patients. However, previous studies in this area have focused on childhood immunizations, and it is unknown whether and to what extent CAM practitioners may influence the vaccination behavior of their adult patients. The purpose of this study was to describe vaccination coverage levels of adults aged ≥ 18 years according to their CAM use status and determine if there is an association between CAM use and adult vaccination coverage. Methods Data from the 2002 National Health Interview Survey, limited to 30,617 adults that provided at least one valid answer to the CAM supplement, were analyzed. Receipt of influenza vaccine during the past 12 months, pneumococcal vaccine (ever), and ≥ 1 dose of hepatitis B vaccine was self-reported. Coverage levels for each vaccine by CAM use status were determined for adults who were considered high priority for vaccination because of the presence of a high risk condition and for non-priority adults. Multivariable analyses were conducted to evaluate the association between CAM users and vaccination status, adjusting for demographic and healthcare utilization characteristics. Results Overall, 36% were recent CAM users. Among priority adults, adjusted vaccination coverage levels were significantly different between recent and non-CAM users for influenza (44% vs 38%; p-value < 0.001) and pneumococcal (40% vs 33%; p-value < 0.001) vaccines but were not significantly different for hepatitis B (60% vs 56%; p-value = 0.36). Among non-priority adults, recent CAM users had significantly higher unadjusted and adjusted vaccination coverage levels compared to non-CAM users for all three vaccines (p-values < 0.001). Conclusion Vaccination coverage levels among recent CAM users were found to be higher than non-CAM users. Because CAM use has been increasing over time in the U.S., it is important to continue monitoring CAM use and its possible influence on receipt of immunizations among adults. Since adult vaccination coverage levels remain below Healthy People 2010 goals, it may be beneficial to work with CAM practitioners to promote adult vaccines as preventive services in keeping with their commitment to maintaining good health.